Study on pollutants formation under knocking combustion conditions using an optical single cylinder SI research engine - Karvountzis-Kontakiotis, Apostolos; Vafamehr, Hassan; Cairns, Alasdair; Peckham, Mark (Elsevier, 2018)
The aim of this experimental study is to investigate the pollutants formation and cyclic emission variability under knocking combustion conditions. A great number of studies extensively describe the phenomenon of knock and its combustion characteristics as well as the effect of knock on engine performance; however the impact of knocking combustion on pollutants formation and how it affects cyclic emission variability has not been previously explored. In this study, an optical single cylinder SI research engine and fast response analyzers were employed to experimentally correlate knocking combustion characteristics with cyclic resolved emissions from cycle to cycle. High-speed natural light photography imaging and simultaneous in-cylinder pressure measurements were obtained from the optical research engine to interpret emissions formation under knocking combustion. The test protocol included the investigation of the effect of various engine parameters such as ignition timing and mixture air/fuel ratio on knocking combustion and pollutant formation. Results showed that at stoichiometric conditions by advancing spark timing from MBT to knock intensity equal to 6 bar, instantaneous NO and HC emissions are increased by up to 60% compared to the MBT operating conditions. A further increase of knock intensity at the limits of pre-ignition region was found to significantly drop NO emissions. Conversely, it was found that when knocking combustion occurs at lean conditions, NO emissions are enhanced as knock intensity is increased.